Physiology of Growth and Development of Fruits and Seeds of Common Beans - Ayres, Samara Dayse da Luz; Nóbrega, Jackson Silva; Bruno, Riselane de Lucena Alcântara; Oliveira, Ademar Pereira de; Alves, Edna Ursulino; Belarmino, Karialane da Silva; Ribeiro, Wellington Souto; Andrade, Alberício Pereira de (Journal of Agricultural Studies, 2021)
Common beans are one of the most economically important legumes in the world. The determination of the ideal harvesting period may coincide with the maximum seed quality and vigor. Thus, the objective was to evaluate the physiology of growth and development of fruits, seeds and seedlings of two cultivars of common beans. To this end, two cultivars of common beans were used: the “Macarrão Trepador” and “Rasteiro Fartura” harvested every five days after anthesis (DAA). The pods were harvested and sent to the laboratory for seed analysis and extraction. In the laboratory, biometric characteristics of fruits and seeds, physiological quality (germination and vigor) and chemical composition of seeds were evaluated. The physiological maturity of “Macarrão Trepador” and “Rasteiro Fartura” cultivars occurred at 35 DAA, during which the seeds had the maximum dry matter and the minimum water content. The chemical composition of the seeds of both cultivars was similar, except for lignin, whose content was higher in “Rasteiro Fartura” cultivar at 25 DAA. The color and dry mass of fruits and seeds, germination percentage, first germination count, germination speed index and average germination time are the indicators that help in determining the physiological maturity point.